Assessing an Innovative Virtual Museum Application using Technology Acceptance Model - Shinta Puspasari; Ermatita; Zulkardi (IJID (International Journal on Informatics for Development), 2022)
This study discusses the assessment of a virtual museum application development based on machine learning models for Palembang culture education through the Sultan Mahmud Badaruddin II museum cultural heritage by using the Technology Acceptance Model approach. The application was tested to measure the user acceptance of the application and pre-test and post-test to measure the effect size of the application as a learning media. A total of N=32 student participants were involved in testing the Sultan Mahmud Badaruddin II innovative virtual museum application for museum visitors was dominated by students who came to the museum to learn the culture and history of Palembang. Hypothesis testing results show that the perceived usefulness and perceived ease of use variables do not affect the attitude toward the use of the innovative virtual museum application. The attitude toward the use of the variable affects the behavioural intention to use, which directly also has a moderate effect on the actual use of the application where the dependent variables have the value of R2 > 0.5. The developed app is recommended as alternative learning media during a pandemic where the app testing participants express interest in using the app to enhance the Palembang culture learning experience.